The Stunting Education at Tambak Sarinah Village for Save the Young Generation: Stunting Education at Tambak Sarinah - Mi'rajunnisa Aditya Putra Pratama, Dwi Wanda Umami Fauzi, Maulida Azzahra, Maharani Calista, Mahmuda (UMBanjarmasin, 2024)
Stunting is a global problem that can affect health and hinder children's growth and development. Indonesia is known as a country that has many cases of stunting, one of which is in Tambak Sarinah, Tanah Laut. To overcome this problem, Muhammadiyah Banjarmasin University (UM Banjarmasin) students carried out community service with the theme of stunting, which aims to increase the level of public knowledge about stunting so that people avoid stunting. The method used is a combination of observation, interviews, counseling, mentoring, and practice. The program results show that the level of public knowledge about stunting has increased after being given education about stunting.